Which guide to men's health - Carroll, Steve (Which? Ltd LondonGB, 1999)
Provides health advice and guidelines related to the needs of men. Describes body systems and organs; and examines topics including: nutrition, sexual health, and fatherhood. Provides an A-Z of common health problems experenced by men including: angina, athlete's foot, bronchitis, cancers, dementia, depression, diabetes, epilepsy, snoring and rheumatoid arthritis.